PELATIHAN PENGGUNAAN MEDIA ONLINE UNTUK MEMASARKAN BARANG PADA IBU-IBU PKK RT.01 RW. 11 KEDUNG KANDANG MALANG - Novi Nugrahani; Atika Syuliswati; Siti Amerieska; Aang Afandi; Ahmad Jarnuzi (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2022)
The purpose of this Community Service activity is to provide marketinng training with online media namely Instagram. Moms households can take advantage of the internet by doing online business without having to leave the house so that you can keep an eye on your family. This community service was held on September 13, 2020 by inviting all member of PKK Grup RT. 01 RW. 11 Kedung Kandang Malang. The training was carried out materials and discussion. The presence of the team majoring in Accountancy at the State Polytechnic of Malang has provide enlightenment and new knowledge that is quite meaningful for all participants. Thing This is proven after Community Service activities, several mothers have started selling businesses online